Complementary dietary treatment using lysine-free, arginine-fortified amino acid supplements in glutaric aciduria type I: a decade of experience - Kölker, Stefan; Boy, Nikolas; Heringer-Seifert, Jana; Müller, Edith; Hoffmann, Georg F.; Haege, Gisela; Burgard, Peter (Molecular genetics and metabolism, 2012)
The cerebral formation and entrapment of neurotoxic dicarboxylic metabolites (glutaryl-CoA, glutaric and 3-hydroxyglutaric acid) are considered to be important pathomechanisms of striatal injury in glutaric aciduria type I (GA-I). The quantitatively most important precursor of these metabolites is lysine. Recommended therapeutic interventions aim to reduce lysine oxidation (low lysine diet, emergency treatment to minimize catabolism) and to enhance physiologic detoxification of glutaryl-CoA via formation of glutarylcarnitine (carnitine supplementation). It has been recently shown in Gcdh−/− mice that cerebral lysine influx and oxidation can be modulated by arginine which competes with lysine for transport at the blood-brain barrier and the inner mitochondrial membrane [Sauer et al., Brain 134 (2011) 157-170]. Furthermore, short-term outcome of 12 children receiving arginine-fortified diet showed very promising results [Strauss et al., Mol. Genet. Metab. 104 (2011) 93-106]. Since lysine-free, arginine-fortified amino acid supplements (AAS) are commercially available and used in Germany for more than a decade, we evaluated the effect of arginine supplementation in a cohort of 34 neonatally diagnosed GA-I patients (median age, 7.43years; cumulative follow-up period, 221.6patientyears) who received metabolic treatment according to a published guideline [Kölker et al., J. Inherit. Metab. Dis. 30 (2007) 5-22]. Patients used one of two AAS product lines during the first year of life, resulting in differences in arginine consumption [group 1 (Milupa Metabolics): mean=111mg arginine/kg; group 2 (Nutricia): mean=145mg arginine/kg; p<0.001]. However, in both groups the daily arginine intake was increased (mean, 137mg/kg body weight) and the dietary lysine-to-arginine ratio was decreased (mean, 0.7) compared to infants receiving human milk and other natural foods only. All other dietary parameters were in the same range. Despite significantly different arginine intake, the plasma lysine-to-arginine ratio did not differ in both groups. Frequency of dystonia was low (group 1: 12.5%; group 2: 8%) compared with patients not being treated according to the guideline, and gross motor development was similar in both groups. In conclusion, the development of complementary dietary strategies exploiting transport competition between lysine and arginine for treatment of GA-I seems promising. More work is required to understand neuroprotective mechanisms of arginine, to develop dietary recommendations for arginine and to evaluate the usefulness of plasma monitoring for lysine and arginine levels as predictors of cerebral lysine influx.
Gesehen am 08.11.2018